Relação hídrica e teor de clorofila em dois cultivares de arroz submetido à deficiência hidrica e adubação silicatada - Moro, Adriana Lima; Broetto, Fernando [UNESP]; Moro, Edemar (My University, 2015)
Plants under water stress jeopardize physiological processes and production capacity. Silicon is a nutrient which provides better growth to rice plants grown in an environment under water stress. This element reduces losses of water by transpiration, improving the physiological functions of the plant. The objective of this study was to evaluate the relationship between water stress and the silicon effect on two rice cultivars under pigments, to determine relative water content (RWC), transpiration and dry matter. A completely randomized and factorial (4x2) design was used with four replicates. Treatments consisted of four matric potential of water in the soil water (-10, -30, -50 and -70 kPa) in association with two amendments for soil acidity (lime and magnesium and calcium silicate). An increase was observed in the content of chlorophyll a by the addition of silicon to cv. Curinga during the flowering stage An increase in the RWC for both cultivars and in all phenological phases was observed after silicon addition. Transpiration rate was lower in both cultivars as of the booting stage at the higher tensions of -50 and -70kPa. An increase in dry matter for both cultivars after silicon addition was observed during the grain filling stage even considering the intensity of water stress.
Water relationship and chlorophyll content in two rice cultivars under water stress and silicon fertilization
Keywords: Potential; Relative water content; Transpiration